Go-Ethereum for electronic voting system using clique as proof-of-authority - Basilius Bias Astho Christyono; Moeljono Widjaja; Arya Wicaksana (Universitas Ahmad Dahlan, 2021)
Current advances in information technology have brought about significant changes, including ways to carry out elections using computer technology known as e-voting. Blockchain underlies the popularity of the digital currency Bitcoin and some other digital money, sparking the start of a new era of Internet use, including electronic voting (e-voting) system. In this work, we proposed designing and implementing an evoting system powered by the Ethereum blockchain. We used real-world data from the Indonesian Election Commission (KPU) with 26 candidates and 15,725 voters from the Jelupang sub-district. The testing and evaluation results using three miners in the blockchain show that the system could commit around 23 transactions per second. All 15,725 votes are committed to the blockchain successfully within 12.75 minutes. The total time required for creating all blockchain accounts is 13.4 hours.